The US-Mexico-Canada Agreement: the new gold standard to enforce investment treaty protection? - Orlando F. Cabrera C (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
In the current investment arbitration crisis, the United States-Mexico-Canada Agreement (USMCA) presents a unique solution. Governments concerned with regulatory chill should adopt the USMCA model if they want to reduce the risk of ISDS claims related to the regulation of health, national security, morals and the environment.
Keywords: 330